Effect of Sweet Potato Vine Planting Orientation on the Growth and Yield of Sweet Potato/Maize Intercropping System in Makurdi, Southern Guinea Savanna, Nigeria - J.A, Idoko,; B.W, Akaazua,; A.T, Aduwele, (International Journal of Scientific Research and Management (IJSRM), 2018)
Two field experiments were carried out during the cropping seasons of 2016 and 2017 at the Teaching and Research Farm of the University of Agriculture, Makurdi, Benue State, Nigeria. The experiments sought to determine the effect of sweet potato vine orientation on growth and yield of sweet potato/maize intercropping system with a view to improve the productivity of maize/sweet potato intercropping in Makurdi. The experiment was a 2 x 2 x 3 split-split plot laid out in randomized complete block design with three replications. The main plot treatments were two cropping systems [sole cropping (sweet potato, maize), intercropping (sweet potato + maize)].The sub plot treatments were made up of two maize varieties (pop.66SR/ACR.91 SUWAH 1-SR and M2: pool18R/AK94DMRESR-Y). The sub-sub plot treatments comprised of three (3) sweet potato vine orientations (incline, loop and horizontal). The result obtained from the experiment showed sole cropping gave higher cob length, number of seeds per cob, cob weight, grain yield and 100-seed weight of maize than intercropping in both years. In all years, pool18R/AK94DMRESR-Y produced higher yield and yield parameters of maize than pop.66SR/ACR.91 SUWAH 1-SR irrespective of the cropping system. In 2016 and 2017, horizontal vine orientation gave higher vine length, root diameter, root length, number of saleable roots per hectare and weight of saleable roots than all the other vine orientations. Intercropping with pop.66SR/ACR.91 SUWAH 1-SR gave higher growth and yield parameters than intercropping with pool18R/AK94DMRESR-Y. All intercrop combinations had LER figures above 1.0 and LEC values above 0.25 in both years. CR values of sweet potato were consistently higher than those of maize in all intercrop combinations in 2016 and 2017